A Review of the “Non - Grainization” of Cultivated Land - Xia, Liheng; Wang, Kun (International Journal of Social Sciences and Public Administration, 2025)
This paper provides a comprehensive review of the “non - grainization” of cultivated land. It analyzes the current situation, causes, and impacts of cultivated land non - grainization, and then proposes corresponding countermeasures. Through a systematic review of relevant literature, it is found that the non - grainization of cultivated land is a complex issue involving multiple factors such as economic, social, and policy aspects. The rational use of cultivated land and the guarantee of grain production are of great significance for national food security and sustainable agricultural development.